ORAL MISOPROSROL VERSUS INTRAVENOUS OXYTOCIN INFUSION IN INDUCTION OF LABOUR IN PROM (The Research of Medical Science Review, 2025)
BACKGROUND: Induction of labor (IOL) is defined as the artificial stimulation of uterine contractions before the spontaneous onset of labor at term. Approximately 20% of pregnancies require induction due to increased risks associated with continuation of pregnancy. Common indications include post-term pregnancy, pre-labor rupture of membranes (PROM), hypertensive disorders, intrauterine fetal death, maternal diabetes, intrauterine growth restriction, chorioamnionitis, oligohydramnios, and intrahepatic cholestasis of pregnancy. While various methods of induction are used including membrane sweeping, mechanical methods, prostaglandins, and oxytocin clinical guidelines differ regarding their recommendations. Notably, the NICE guidelines do not endorse the use of misoprostol, although other international bodies support its use.OBJECTIVES: To determine and compare: The frequency of successful induction of labor among PROM patients induced with oral misoprostol versus intravenous oxytocin. The frequency of maternal complications, including hyperstimulation and postpartum hemorrhage, in both groups.METHODS: A randomized clinical trial was conducted at the Maternal and Child Health Institute (MCHI), DIMS, Islamabad. A total of 450 pregnant women with PROM were randomly assigned into two equal groups: Group A received oral misoprostol and Group B received intravenous oxytocin. Data on induction success and maternal complications were collected and analyzed. Chi-square test was applied to assess statistical significance, with a p-value < 0.05 considered significant.RESULTS: Successful induction occurred in 84.4% of women in Group A (misoprostol) and 77.8% in Group B (oxytocin) (p = 0.073). Hyperstimulation was significantly higher in the misoprostol group (8.0%) compared to the oxytocin group (3.1%) (p = 0.021). Although postpartum hemorrhage and fetal distress were more common in the misoprostol group, these differences were not statistically significant (p > 0.05).CONCLUSION: Oral misoprostol is slightly more effective than intravenous oxytocin in achieving successful labor induction in PROM patients; however, it is associated with a significantly higher rate of uterine hyperstimulation. Clinicians should carefully weigh efficacy against safety when selecting the method of induction in PROM cases..